Clinical Study and Microbiological Analysis of Periodontopathogenic Microflora Analyzed among Children and Adolescents with Cardiovascular Diseases Compared to Group with Good General Status - Oana Chipirliu; Marian Viorel Crăciun; Madalina Nicoleta Matei (MDPI AG, 2024)
Periodontal diseases, as an important part of oral pathology, present different characteristics when affecting children and adolescents or young adults. Studies have shown that adolescence and childhood are closely related to a high risk of periodontal disease, but the follow-up for periodontal health or damage at this age has been insufficiently appreciated until now. The aim of this study was to identify subgingival microorganisms using a real-time polymerase chain reaction (PCR) in a group of children and adolescents aged 7-17 years with and without cardiovascular disease. The group of 62 subjects with gingival inflammation and poor hygiene was divided into two groups according to general condition: 31 subjects with carduivascular disease (group A) and 31 subjects without cardiovascular disease (group C). Subjects were examined in the initial consultation, the state of hygiene and periodontal inflammation was assessed using the plaque index (PI) and gingival index (GI), and samples were taken from the gingival sulcus using sterile paper cones to determine nine subgingival microorganisms. Nine subgingival microorganisms were identified: Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Treponema denticola (Td), Tannerella forsythias (Tf), Prevotella intermedia (Pi), Peptostreptococcus (Micromonas) micros (Pm), Fusobacterium nucleatum (Fn), Eubacterium nodatum (En), and Capnocytophaga gingivalis (Cg). The patients were included in a specialist treatment program which aimed to relieve the inflammatory condition, remove local irritative factors, and train the patients to perform proper oral hygiene at home by using primary and secondary oral hygiene products. Subjects were reevaluated 3 months after treatment, when measurements for the PI and GI and microbiological determinations were repeated. The results showed a predominance of subjects aged 16-17 years (12.4%). Among the subjects with marked gingival inflammation, the male gender was predominant (58.06%). The PI values changed considerably after treatment, with lower values in patients presenting a general condition without cardiovascular disease (PI = 8.10%) compared with the patients with cardiovascular disease (PI = 13.77%). After treatment, the GI showed considerable changes in both groups. Red, orange, and purple complex microorganisms were found before treatment and decreased considerably after treatment in both groups. The highest values were found for Treponema denticola (140,000 (1.4 × 105)) in patients with cardiovascular disease and generalized gingival inflammation. Of the pathogenic microorganisms, the most common was Tannerella forsythia in 52 patients before treatment, and red microorganisms considerably appeared in only 10 patients after treatment. Capnocytophaga gingivalis remained constant both in the diseased state and after treatment and was consistent with periodontal health. Children with cardiovascular diseases had a higher prevalence of gingival manifestations. The composition of the subgingival microbial plaque was directly influenced by the degree of oral hygiene, but the response to specialized treatment was also influenced by the general health status. The results of this study support the conclusion that periodontal pathogens appear and multiply in the absence of proper hygiene in childhood after the eruption of permanent teeth, and their action leads to the initiation of periodontal diseases.